FREE DIGITAL TRANSPORTATION INNOVATION FOR EQUITABLE PUBLIC ACCESS IN TUBAN REGENCY - Kardatus Boris Hulu; Amirul Mustofah; Aris Sunarya (International Journal of Multidisciplinary Reseach, 2026)
Limited access to public transportation in regency areas remains a structural barrier to equitable access to basic services. This study analyzes the implementation of the Si Mas Ganteng Program (Tuban Free Digital Transportation Management System) as a digital public service innovation in Tuban Regency, its contribution to equitable community access, and the factors supporting and constraining implementation. The study employed a qualitative case study approach. Data were collected through in-depth interviews with seven purposively selected informants, including Transportation Agency officials, drivers, service users, a village head, and an academic, supported by observation and document analysis. Data were interpreted using Rogers’ Diffusion of Innovations Theory, Edwards III’s Policy Implementation Theory, and Denhardt and Denhardt’s New Public Service paradigm. The findings indicate that registered users increased by 1,378% from 2022 to 2024, supported by strong implementer commitment and the program’s free service, which encouraged trialability. Nevertheless, limited fleets, weak coordination across government levels, low digital literacy among older residents, and urban-centered user distribution continue to constrain equitable access. The program reflects New Public Service principles by prioritizing citizen welfare over market logic and offers a relevant model for inclusive digital public transportation in other regions.